The distribution of the islets of Langerhans in pancreas of euglycemic spontaneously hypertensive rats - T. V. Abramova (Patologìâ)
Considering the fact, that pancreatic beta cells are responsible for production of all insulin needed to maintain the glucose homeostasis, the problem of beta cells pull control in patients with hypertension is rather topical. It cannot be ruled, that genetical defects of congenital hypertension formation can affect the mechanisms of maintaining of the cell mass of pancreatic endocrinocytes and lead to violation of glucose metabolism and diabetes mellitus development. Moreover, the violation of cytoarchitectonics of pancreatic islets of Langerhans may lead to impairment of the insulin secretion, which can be due to local impairment of the blood circulation in patients with hypertension.